PERANCANGAN SISTEM INFORMASI ABSENSI KARYAWAN BERBASIS WEB PADA KEDAI KOPI KAMU MENGGUNAKAN METODE AGILE DEVELOPMENT: PERANCANGAN SISTEM INFORMASI ABSENSI KARYAWAN BERBASIS WEB PADA KEDAI KOPI KAMU MENGGUNAKAN METODE AGILE DEVELOPMENT - Haikal, Muhammad; Widiarina; Junadi, Bambang (Blueprint Journal, 2025)
The rapid development of information technology has encouraged various organizations to shift from manual systems to digital based management. One of the essential aspects in human resource management is an efficient, accurate, and easily accessible employee attendance system. Kedai Kopi Kamu, as a micro, small, and medium enterprise (MSME), previously relied on a manual attendance system, which often caused problems such as delays in data recap, inaccurate recording, and difficulties in monitoring employee attendance. To overcome these issues, this study aims to design a web-based employee attendance information system using the Agile Development method. The objective of this research is to develop a system capable of facilitating real-time recording and reporting of employee attendance. The Agile Development method was applied due to its iterative, flexible, and collaborative approach between developers and users. The system development process consisted of several stages, including requirement analysis, design, development, testing, implementation, and evaluation. Modeling tools such as Use Case Diagram, Activity Diagram, and Entity Relationship Diagram (ERD) were utilized to describe the system workflow and data structure. The implementation results indicate that the developed system operates effectively and meets user requirements. System testing was conducted using the Black-Box Testing method, which verified that all system functions performed according to specifications. The web-based attendance system successfully improved the efficiency, accuracy, and transparency of employee attendance management at Kedai Kopi Kamu. Furthermore, the application of the Agile method proved to be effective in supporting software development processes within MSMEs that require rapid adaptation to changing user needs.